UNFINISHED PARADIGM: A SYSTEMATIC LITERATURE REVIEW OF REGENERATIVE TOURISM ACROSS CULTURES, GOVERNANCE, AND BEHAVIOUR (2001–2024) (Contemporary Journal of Social Science Review, 2025)
Regenerative tourism has emerged as a compelling paradigm that seeks to move beyond the sustainability discourse by fostering net-positive outcomes for destinations, ecosystems, and communities. This study presents a systematic literature review of 45 peer-reviewed articles published between 2001 and 2024, synthesizing theoretical, empirical, and methodological contributions to the field. Guided by the PRISMA framework, publications were retrieved from major databases and analyzed to identify conceptual foundations, patterns of application, and persistent challenges. Findings indicate that regenerative tourism is theoretically plural, drawing from resilience theory, ecological restoration, political economy critiques, behavioural psychology, and Indigenous epistemologies. Empirical studies demonstrate significant geographical variation: in the Pacific and Latin America, regeneration aligns with Indigenous worldviews and socio-political projects; in Europe and North America, it is embedded within governance frameworks; in Africa, it is tied to conservation and community benefit-sharing. More recent scholarship highlights the role of tourists themselves, with behavioural factors such as climate advocacy and social norms shaping regenerative intentions, albeit with contradictions between values and practices. Despite its promise, regenerative tourism faces definitional ambiguity, institutional inertia, measurement challenges, and risks of discursive capture. Two recent 2024 studies reinforce these tensions, revealing both governance-level barriers and behavioural complexities. This review identifies critical research gaps, including the need for conceptual boundary clarity, context-sensitive metrics, strategies to bridge the attitude–behaviour gap, and stronger engagement with Indigenous epistemologies. I propose that regenerative tourism should be viewed as an unfinished project: adaptive, plural, and contested, yet holding transformative potential to reshape tourism as a reciprocal rather than extractive practice.